Достоевский о поляках — поляки о Достоевском: метастереотипность как имагологическая проблема - Мальцев, Леонид (Studia Rossica Posnaniensia, 2017)
In the article, Jerzy Stempowski's essay The Poles in Novels by Dostoyevsky is analyzed in terms of its imagological aspect. Polish motifs in the novel The Brothers Karamazov are investigated in connexion with the writer's religious philosophy and existential consciousness.